Soft Skills of Tourism Frontliners Workers in Melaka - Syed Najmuddin, Syed Hassan; Mohd Fauzi, Kamarud-din; Muhd Akmal Noor, Rajikon; Rosli, Saadan; Ahmad Rozelan, Yunus; Amir, Aris; Ramlee, Mustapha; Mustafa, Omar (Penerbit Universiti Teknikal Malaysia Melaka, 2010)
This exploratory study aims to identify the need of generic skills in the tourism industry in Melaka. The subjects consist of 70 front liners, male (N=29) and female (N= 41) who work at recreational and hotel sectors in Melaka. Subjects responded to the Social Inventory for Melaka Tourism Sector (Inventori Kemahiran Sosial Pekerja Pelancongan Melaka). The inventory has a fairly high reliability of 0.85 – 0.88, hence suggesting its pragmatic utility. Findings of the study show that Melaka tourism front liners views the importance of generic skills as follows; ethiques and knowledge (Min= 4.3, SD: .70), personality (Min= 3.9, SD: .68), attire (Min= 3.6, SD: .37) and language (Min= 3.6, SD: .49).